Allogeneic Bone Marrow–Derived Mesenchymal Stem Cell Safety in Idiopathic Parkinson's Disease. Issue 8 (27th March 2021) - Schiess, Mya; Suescun, Jessika; Doursout, Marie‐Francoise; Adams, Christopher; Green, Charles; Saltarrelli, Jerome G.; Savitz, Sean; Ellmore, Timothy M.
ABSTRACT: Background: Neuroinflammation plays a key role in PD pathogenesis, and allogeneic bone marrow–derived mesenchymal stem cells can be used as an immunomodulatory therapy. Objective: The objective of this study was to prove the safety and tolerability of intravenous allogeneic bone marrow–derived mesenchymal stem cells in PD patients. Methods: This was a 12‐month single‐center open‐label dose‐escalation phase 1 study of 20 subjects with mild/moderate PD assigned to a single intravenous infusion of 1 of 4 doses: 1, 3, 6, or 10 × 10 6 allogeneic bone marrow–derived mesenchymal stem cells/kg, evaluated 3, 12, 24, and 52 weeks postinfusion. Primary outcome safety measures included transfusion reaction, study‐related adverse events, and immunogenic responses. Secondary outcomes included impact on peripheral markers, PD progression, and changes in brain perfusion. Results: There were no serious adverse reactions related to the infusion and no responses to donor‐specific human leukocyte antigens. Most common treatment‐emergent adverse events were dyskinesias (20%, n = 4) with 1 emergent and 3 exacerbations; and hypertension (20%, n = 4) with 3 transient episodes and 1 requiring medical intervention. One possibly related serious adverse event occurred in a patient with a 4‐year history of lymphocytosis who developed asymptomatic chronic lymphocytic leukemia. Peripheral inflammation markers appear to be reduced at 52 weeks in the highest dose including, tumor necrosis factor‐α ( P  < 0.05), chemokine (C‐C motif) ligand 22 ( P  < 0.05), whereas brain‐derived neurotrophic factor ( P  < 0.05) increased. The highest dose seems to have demonstrated the most significant effect at 52 weeks, reducing the OFF state UPDRS motor, −14.4 ( P  < 0.01), and total, −20.8 ( P  < 0.05), scores. Conclusion: A single intravenous infusion of allogeneic bone marrow–derived mesenchymal stem cells at doses of 1, 3, 6, or 10 × 10 6 allogeneic bone marrow–derived mesenchymal stem cells/kg is safe, well tolerated, and not immunogenic in mild/moderate PD patients. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society